Selective Synthesis of Tetrahydroisoquinoline and Piperidine Scaffolds by Oxidative Ring Opening/Ring Closing Protocols of Substituted Indenes and Cyclopentenes - Anas Semghouli; László Drahos; Jianlin Han; Loránd Kiss; Melinda Nonn (ChemistryOpen)
Abstract Novel tetrahydroisoquinoline and piperidine derivatives were selectively synthesized from substituted indenes or cyclopentenes. The process starts with an oxidative cleavage of the ring olefin bond, which gives reactive diformyl intermediates. By a ring‐closing step using chiral (R) or (S) α‐methylbenzylamine under a reductive amination protocol facilitated ring formation with ring expansion of the corresponding nitrogen‐containing heterocycles. The stereocontrolled methodology enabled accurate control of the stereochemistry of the final products. Additionally, the synthesized amino acid derivatives possessing an aryl moiety in their structure may be relevant building blocks for foldamer chemistry.